MODEL KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN KOMITMEN GURU DI UPTD SMP NEGERI 3 PEUSANGAN) - Marthunis Rahmawaty; Marwan Marwan; Jamaluddin Jamaluddin (Hijri, 2025)
This study aims to analyze the model of transformational leadership practiced by the principal in building teacher commitment at UPTD SMP Negeri 3 Peusangan. Transformational leadership is a leadership approach that emphasizes moral influence, inspirational motivation, individualized consideration, and intellectual stimulation to create positive and sustainable change. This research employed a qualitative approach using a case study design, with data collected through interviews, observation, and documentation. The research subjects included vice principals in charge of student affairs and curriculum, teachers, school operators, and the school committee. The findings reveal that all four dimensions of transformational leadership were effectively implemented. Idealized influence was demonstrated through the principal's exemplary behavior and moral integrity; inspirational motivation was reflected through reflective communication and open appreciation; individualized consideration was realized through support for teachers' personal needs and professional development; and intellectual stimulation was evident in the encouragement of innovative teaching practices through training, facilities, and recognition of creative ideas. These leadership practices fostered teacher commitment in affective, continuance, and normative dimensions within a participatory, humanistic, and reflective work environment. The study indicates that transformational leadership can serve as a key strategy to strengthen teacher loyalty, engagement, and motivation in carrying out educational responsibilities sustainably